Investigation of Conceptual and Operational Understanding Processes of Eighth Grade Students to Identities and Factorization - Aytaç Kurtuluş, İnci Ünlüer, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this study is to examine the conceptual and procedural understanding processes of eighth grade students through syllabi based on 5E Learning Cycle for the subjects of identities and factoring. In this qualitative research, the teaching experiment model was used. The research was carried out with 20 students studying in a public secondary school in Istanbul. The levels of mathematical success of these students were, high, medium and low, and thus were heterogeneous. A readiness test was applied to determine the prior knowledge and skills of students about identities and factoring. According to the data obtained from this test, three different syllabi were designed and implemented to examine students' conceptual and procedural understanding processes for identities and factoring. During the 12-hour teaching experiment, data were collected via researcher's observation notes, readiness test, activity handouts and worksheets. The data were analyzed using descriptive analysis technique. According to the results of the readiness test, students could adequately express their procedural knowledge about algebraic expressions in 6th and 7th grades; however, it was inferred that their conceptual knowledge wasn‟t complete. Furthermore, evaluations were made during the syllabi which were prepared within the scope of the 5E Learning Cycle. According to the data obtained from these evaluations, students were able to express the concept of identity, which is one of the learning outcomes of identities and factoring, in terms of both conceptual and procedural knowledge. However, it was observed that they were not able to completely achieve procedural and conceptual understanding of the identity (a -b) ², and procedural understanding of the identity a² -b².